Flouting Maxims In Series Never Have I Ever - Ida Ayu Mas Maura Dwi Handayani; Anak Agung Sagung Shanti Sari Dewi; I Made Rajeg (CV. Ulil Albab Corp, 2022)
Abstract: The title of this study is “Flouting Maxims in Series Never Have I Ever”. It aim to analyze the types of flouting maxims used by the character in a series. The data were taken from the first episode of the first season of a famous American comedy series entitled Never Have I Ever. They were collected using observation and documentation methods. Then, they were analyzed using the theory of Flouting Maxims proposed by Grice (1975). The results showed that all the types of flouting maxims, namely flouting maxim of quantity, flouting maxim of quality, flouting maxim of relation, and flouting maxim of manner, were used by the characters in their interaction with each other.